Pengaruh Islamophobia Terhadap Peningkatan Kekerasan Muslim Di Perancis - Pradipta, Christian Aditya (Global and Policy Journal of International Relations, 2016)
ABSTRACT9/11 tragedy in United States was the one of important thing that pushed Islamophobia issue to be global phenomenon. Integrated world not only pushes populations mobility, but help to spread out the fear about Islam easily. French who believes about Seculerism, seeing Muslim as incompatible with them. French feels afraid the existence and dominated by Muslim through the growth of population and some extrimist terorist attack. Dominated and threaten feelings push French doing violences to Muslim. It also matches with Huntington’s Clash of Civilization. It explained that West has high posibility to get clash with Islam Civilizations. This research is going to explain how clash of civilizations, existences needs, and incompatibility push French doing violences to Muslim at France 2002-2015.Keywords: French, Islamophobia, Violence, ThreatenDOI : https://doi.org/10.33005/jgp.v4i02.1920